2017
DOI: 10.1039/c6pp00166a
|View full text |Cite
|
Sign up to set email alerts
|

meso-Acetoxymethyl BODIPY dyes for photodynamic therapy: improved photostability of singlet oxygen photosensitizers

Abstract: We report two BODIPY based photosensitizers (Br2BOAc and I2BOAc) featuring an acetoxymethyl substituent at the meso-position. These photosensitizers show improved photostability against singlet oxygen, when compared to a BODIPY photosensitizer lacking the acetoxymethyl group. Both compounds were evaluated for photodynamic therapy against HeLa cells and photodynamic inactivation against E. coli bacteria. We show that the compounds readily embed in the lipid membranes of HeLa cervical cancer cells and efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…This compound combined BODIPY and aniline derivative as nitric oxide photodonor, which had an amplified photomortality on melanoma cancer cells. Lincoln et al 106 prepared two small meso-acetoxymethyl BODIPY dyes 27 , which showed improved photostability against singlet oxygen compared to the BODIPY PSs lacking the acetoxymethyl group. Compounds 27 can readily embed in the lipid membranes of Hela cells and efficiently induced light-dependent apoptosis at nanomolar concentration.…”
Section: Recent Development In Anticancer Pssmentioning
confidence: 99%
“…This compound combined BODIPY and aniline derivative as nitric oxide photodonor, which had an amplified photomortality on melanoma cancer cells. Lincoln et al 106 prepared two small meso-acetoxymethyl BODIPY dyes 27 , which showed improved photostability against singlet oxygen compared to the BODIPY PSs lacking the acetoxymethyl group. Compounds 27 can readily embed in the lipid membranes of Hela cells and efficiently induced light-dependent apoptosis at nanomolar concentration.…”
Section: Recent Development In Anticancer Pssmentioning
confidence: 99%
“…Furthermore, it has been found that the heavy atom substituted BODIPY dyes containing an electron-withdrawing acetoxymethyl moiety in the meso-position could be enhanced photostability for the PDT agents. [28][29][30][31][32] Recently, our groups focused attention in the development Ni(II), Zn(II), Cd(II), Co(II), Ru(II), Ir(III), Pt(II), Pd(II), and triorganotin(IV) complexes containing phenylcyanamide derivatives as monodentate ligands in regard to traditional chemotherapy and PDT applications. [33][34][35][36][37][38][39] With the aim of enhancing the photophysical and photobiological properties of BODIPY ligands in cyclometalated Ir(III) complexes, we have designed new monodentate ligand by linking meso-BODIPY ligands to phenylcyanamide ligands.…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks, however, can be potentially circumvented taking advantage of the proneness of the dye to chemical functionalization, through which the photophysical properties could be adjusted. Several works in the literature have considered the use of BODIPY dimers or the introduction of heavy atoms to enhance singlet oxygen production in BODIPYs, yet a balance between high triplet quantum yields and acceptable light/dark toxicity ratio or imaging and therapeutic combined effects, very useful at the first stages of in vivo/in vitro studies and further on in clinical trials, has not been accomplished. In order to design BODIPYs showing an improved spectroscopic profile suitable for singlet oxygen photosensitization and fulfilling the additional clinical conditions, mentioned above, the dissection of the photophysics of the parent compound could provide a valuable basis to subsequently draw clear structure‐photophysics relationships for different derivatives.…”
Section: Introductionmentioning
confidence: 99%